16 Outcomes for home parenteral nutrition patients in northern ireland – a ten year review (2006–2016). (5th April 2017) - Gardiner, E; Murray, E; Rafferty, G; Turner, GB
Abstract : Background: Intestinal failure (IF) patients in Northern Ireland requiring home parenteral nutrition (hPN) are managed in the Belfast Trust by the Nutrition team at Belfast City Hospital. Aim: The aims of this review were to analyse the aetiology of IF; admission rates (particularly those due to catheter related blood stream infections (CRBSI)) and patient outcomes. Method: Electronic records including radiology and microbiology results for all patients on hPN in Northern Ireland from 2006–2016 were reviewed. Results: 86 patients used hPN between 2006–2016. One patient was excluded due to incomplete data. The average age at presentation was 51 (range 19–78). The mean number of days hPN was administered was 1072 (range 23–3834). The most common causes of IF were Crohn's disease (29%), surgical complications (22%) and mesenteric ischaemia (18%). There were 414 admissions in the timescale – 137 admissions were due to CRBSI. The CRBSI rate was 1.5 per 1000 catheter days (previously 1.81 (1994–2014)). 43 patients had no infections (51%) and 10 had >5 infections, accounting for 55% of all CRSBI admissions. The most common organisms identified were Gram negative organisms (38%) Coagulase Negative Staphylococci (34%); and Yeasts (11%). 28% of patients remain on home parenteral nutrition; 21 patients have had restoration of intestinal continuity. Conclusions: Parenteral nutrition remains a safe treatment in the management of intestinal failure. Our CRBSI rate has reduced in the past 10 years, likely due to ongoing patient education and training.